2021
DOI: 10.1002/lary.29421
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Systemic Inflammatory Response in Cases of Temporal Bone Squamous Cell Carcinoma

Abstract: Objective/Hypothesis: Squamous cell carcinoma (SCC) of the temporal bone is an extremely rare condition. This rarity has led to a delay in the establishment of a standard treatment protocol and adequate staging system. Identification of prognostic markers of this disease from a variety of fields is desirable in the establishment of treatment guidelines for temporal bone SCC. The aim of this study is to assess the prognostic role of inflammation-based prognostic scores in cases of temporal bone SCC.Study Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In a Japanese series of 71 TBSCC cases treated with curative intent (radical surgery or chemoradiotherapy), Komune et al [12] reported an absolute white blood cell count higher than 8300 cells/µL as a significant predictor of lower OS (HR, 3.244; 95% CI, 1.177-8.936).…”
Section: White Blood Cell Countsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a Japanese series of 71 TBSCC cases treated with curative intent (radical surgery or chemoradiotherapy), Komune et al [12] reported an absolute white blood cell count higher than 8300 cells/µL as a significant predictor of lower OS (HR, 3.244; 95% CI, 1.177-8.936).…”
Section: White Blood Cell Countsmentioning
confidence: 99%
“…A NLR value of 3.95 was suggested as a possible cut-off for prognostic discrimination. Komune et al [12], in their series of 71 cases, found higher NLR values to be associated with reduced 5-year OS rates, also calculating, using an ROC approach, a NLR value of 3.23 as a prognostically relevant cut-off. They also found PLR values higher than 191.29 to be associated with lower OS.…”
Section: Nlr Plr and Lmrmentioning
confidence: 99%
See 2 more Smart Citations
“…Because malignancy status and drugs used in the treatment of malignancy affect blood parameters and COP-NLR ratios and cause a significant selection bias in the study results. 5 In consequence, the predictive value of the COP-NLR ratio for PCF should be carefully evaluated along with clinical evaluation and other laboratory methods.…”
mentioning
confidence: 99%